Reciprocal Expression Patterns of Placental Leucine Aminopeptidase/Insulin-Regulated Aminopeptidase and Vasopressin in the Murine Brain - Goto, Yoshikuni; Nakamura, Takahiro J.; Ogawa, Kenji; Hattori, Akira; Tsujimoto, Masafumi (Frontiers in Molecular Biosciences, 2020)
Placental leucine aminopeptidase/insulin-regulated aminopeptidase (P-LAP/IRAP) regulates vasopressin and oxytocin levels in the brain and peripheral tissues by controlled degradation of these peptides. In this study, we determined the relationship between P-LAP/IRAP and vasopressin levels in subregions of the murine brain. P-LAP/IRAP expression was observed in almost all brain regions. The expression patterns of P-LAP/IRAP and vasopressin indicated that cells expressing one of these protein/peptide were distinct from those expressing the other, although there was significant overlap between the expression regions. In addition, we found reciprocal diurnal rhythm patterns in P-LAP/IRAP and arginine vasopressin (AVP) expression in the hippocampus and pituitary gland. Further, synchronously cultured PC12 cells on treatment with nerve growth factor (NGF) showed circadian expression patterns of P-LAP/IRAP and enzymatic activity during 24 h of incubation. Considering that vasopressin is one of the most efficient peptide substrates of P-LAP/IRAP, these results suggest a possible feedback loop between P-LAP/IRAP and vasopressin expression, that regulates the function of these substrate peptides of the enzyme via translocation of P-LAP/IRAP from intracellular vesicles to the plasma membrane in brain cells. These findings provide novel insights into the functions of P-LAP/IRAP in the brain and suggest the involvement of these peptides in modulation of brain AVP functions in hyperosmolality, memory, learning, and circadian rhythm.